EFEKTIVITAS PENGGUNAAN MEDIA WORDWALL BERBASIS KEARIFAN LOKAL BUOL DALAM MENINGKATKAN HASIL BELAJAR IPAS SISWA KELAS IV SDN 7 BOKAT - Alissah; Mustakim; Rudini, Moh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effectiveness of using Buol local wisdom-based interactive Wordwall learning media in improving the IPAS learning outcomes of fourth-grade students at SDN 7 Bokat. The primary problem addressed in this study was the low learning outcomes of students due to the lack of varied and contextual learning media. The research method employed was quantitative with a pre-experimental One Group Pretest-Posttest design. Data collection instruments included validated multiple-choice learning outcome tests, as well as teacher and student activity observation sheets. Data analysis techniques involved normality testing, Paired Sample T-Test, and effectiveness testing using the N-Gain Score. The results showed an increase in process engagement, where the percentage of teacher activity observation sheets increased from 88% in Meeting I to 90% in Meeting II, supported by excellent student activity engagement. In terms of cognitive learning outcomes, the students' minimum score improved from 40 to 70, and the maximum score increased from 70 to 100. The average pre-test score of 46.67 significantly improved to 88.00 in the post-test. Hypothesis testing through the Paired Sample T-Test yielded a significance value of 0.000 < 0.05 with a t-value of -15.101, meaning that H0 was rejected and Ha was accepted. Furthermore, the N-Gain Score effectiveness test reached 78.55%, placing it in the